Differences in access to Emergency Paediatric Intensive Care and care during Transport (DEPICT): study protocol for a mixed methods study - Padmanabhan Ramnarayan; Stephen Morris; Elizabeth S Draper; Christina Pagel; Jo Wray; Sarah E Seaton; Ruth Evans (BMJ Open)
Introduction Following centralisation of UK paediatric intensive care, specialist retrieval teams were established who travel to general hospitals to stabilise and transport sick children to regional paediatric intensive care units (PICUs). There is national variation among these PICU retrieval teams (PICRTs) in terms of how quickly they reach the patient’s bedside and in the care provided during transport. The impact of these variations on clinical outcomes and the experience of stakeholders (patients, families and healthcare staff) is however unknown. The primary objective of this study is to address this evidence gap.Methods and analysis This mixed-methods project involves the following: (1) retrospective analysis of linked data from routine clinical audits (2014–2016) to assess the impact of service variations on 30-day mortality and other secondary clinical outcomes; (2) a prospective questionnaire study conducted at 24 PICUs and 9 associated PICRTs in England and Wales over a 12-month period in 2018 to collect experience data from parents of transported children as well as qualitative analysis of in-depth interviews with a purposive sample of patients, parents and staff to assess the impact of service variations on patient/family experience; (3) health economic evaluation analysing transport service costs (and other associated costs) against lives saved and longer term measurements of quality of life at 12 months in transported children and (4) mathematical modelling evaluating the costs and potential impact of different service configurations. A final work stream involves a series of stakeholder workshops to synthesise study findings and generate recommendations.Ethics and dissemination The study has been reviewed and approved by the Health Research Authority, ref: 2 18 569. Study results will be actively disseminated through peer-reviewed journals, conference presentations, social media, print and broadcast media, the internet and stakeholder workshops.